Inventory of rubber plantations and identification of potential areas for its cultivation in Assam using high resolution IRS data - Pradeep B; Anand S.S; Annamalainathan K; Jacob J; Meti Meti; Shebin S.M (38th Asian Conference on Remote Sensing (ACRS), Space Applications: Touching Human Lives, 23-27 October 2017, Association on Remote Sensing, New Delhi, India.)
To some extent climate, topography and soil of north-eastern states of India are fully or marginally favourable for natural rubber (NR) cultivation but exact geo-spatial locations of these areas under NR cultivation are unknown yet. Geo-spatial technology based identification of NR and potential areas for its cultivation are relevant to find these lands for further expansion of NR plantations to suitable agro-climatic regions to increase domestic NR production.Present study utilized temporal and multi-resolution satellite data (Cartosat merged LISS IV) of Indian Remote Sensing Satellites (IRS) for identification and estimation of spatial extent of NR and wastelands suitable for its cultivation in Assam state of India. Mapping of the wastelands was carried out without interfering areas under food crops, forests, steep valleys and lands which are more suitable for cultivation of food crops. Spatial extent of rubber plantation distribution of Assam was 16872 ha and additionally areas of about 24783 ha of wastelands suitable for NR cultivation have been estimated. Karimkhanj district of Assam has the highest extent of wastelands suitable for NR followed by Karbi Anglong, Kamrup and Gpalpara districts. These four districts alone accounted for about 63.5;of total rubber cultivation and 82.8;of total wastelands estimated from the state. In general, spread and occurrences of NR and wastelands suitable for its cultivation are more in south-western and north-southern districts whereas north-eastern districts of the state are found less areas of wastelands. The study showed usefulness of high resolution satellite data for accurate mapping and estimation of rubber holdings and wastelands suitable for NR cultivation to increase the extent of NR in Assam without conversion of food crops, forests etc. Estimated wastelands can be prioritized in terms of pedo-climatic variables which can serve as a geo-spatial decision support system for planners in NR sector.
Keywords: Cartosat PAN; LISS IV; Natural rubber; North-East; Spectral signature; Wasteland